2020
DOI: 10.1016/j.heliyon.2020.e05023
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and feeding habits of females in public and private Universities in Osun state, Southwestern, Nigeria

Abstract: This study examined the dietary habits, nutritional status and socio-demographic characteristics of female undergraduates in selected public and private Universities in Osun State, Southwestern, Nigeria. The anthropometric assessment of selected respondents consisted measurements of height, weight, body circumferences, body mass index and waist-to-hip ratio of respondents. The food frequency questionnaire technique was adopted to evaluate the feeding/dietary habits using well-constructed questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…In addition, this study showed that normal BMI was prevalent in more than half of the study participants. This was congruent with Ikujenlola et al [24] as well as Alazayani et al [25] who reported that the BMI of the undergraduates was within the normal level.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, this study showed that normal BMI was prevalent in more than half of the study participants. This was congruent with Ikujenlola et al [24] as well as Alazayani et al [25] who reported that the BMI of the undergraduates was within the normal level.…”
Section: Discussionsupporting
confidence: 88%
“…The P.V. System, with a total cost of NGN 284,355,000 (USD 685,357.91), are reliable, cheap, clean and sustainable (Ikujenlola et al, 2020). They can also supply the required amount of energy to the building over the studied period and be cost-effective in the long term.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the total group of men had a limited intake of sausages and cold meats, sometimes consuming less that the recommended portions, and the vast majority of woman also reported the same (Table 2). This suggests that the control policies have an effect on the consumption of this type of food or that the surveyed subjects are of medium-high income, and there is a tendency for those with the lowest income to consume this type of food due to its low cost (Reyes and Santos, 2020;Ikujenlola and Adekoya, 2020). Regarding the nutritional status, most of the university students were of normal weight (n = 95, 55.9%).…”
Section: Discussionmentioning
confidence: 99%